A Test Method for Dynamic Transmission Error of Transmission Gear of High Speed Accessories of Aeroengine - Lou Jianglei; Ma Zhi; Lei Duncai; He Ling (Jixie chuandong)
Aiming at the actual working conditions of high temperature， high speed and heavy oil mist of the accessory transmission gear of aero engine， a set of the gear dynamic transmission error test system is designed and developed based on the principle of the quadruple subdivision of magnetic grid sensor. In this system， the real-time rotation angel of the driving gear and driven gear is respectively measured at the same time by magnetic grid sensor， through the high-speed data acquisition， storage devices of NI and the producer/consumer design pattern of LabVIEW for real-time acquisition and storage of the high-frequency data. Finally， the digital counting method is used to obtain the gear dynamic transmission error curve. The measuring speed of the testing system can reach 40 000 r/min， which is doubled the measurable speed of the previous test system， it can provide data support for vibration analysis and tooth surface design of higher-speed accessories transmission gear.